1999
DOI: 10.1111/j.1532-5415.1999.tb02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Nursing Home Outbreaks of Respiratory Infection with Legionella sainthelensi

Abstract: This report describes outbreaks of legionellosis in two nursing homes, representing the first reported outbreaks of infection caused by Legionella sainthelensi. The association with illness of dietary characteristics indicative of swallowing disorders suggests that aspiration was the most likely mode of infection. The diagnosis of legionellosis should be considered during outbreaks of respiratory infection in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 30 publications
(39 reference statements)
1
22
1
1
Order By: Relevance
“…From this literature it is apparent that L pneumophila serogroup 1 and Legionella longbeachae serogroup 2 were present in the water supplies of Nova Scotia hospitals (13) and that L pneumophila, Legionella micdadei and Legionella dumoffi had been recovered from clinical and or environmental specimens in the Quebec City area (14,15). L pneumophila serogroups 1, 3, 6 and 12, Legionella sainthelensi, and Legionella feelei have been reported from Ontario (16)(17)(18)(19)(20)(21); L pneumophila serogroup 1 from Manitoba (22); and Legionella maccachernii from Saskatchewan (23). Nicolle et al (24) reported nine patients with community-acquired Legionellosis who were hospitalized at the Health Sciences Centre in Winnipeg between 1986 and 1991.…”
Section: Discussionmentioning
confidence: 99%
“…From this literature it is apparent that L pneumophila serogroup 1 and Legionella longbeachae serogroup 2 were present in the water supplies of Nova Scotia hospitals (13) and that L pneumophila, Legionella micdadei and Legionella dumoffi had been recovered from clinical and or environmental specimens in the Quebec City area (14,15). L pneumophila serogroups 1, 3, 6 and 12, Legionella sainthelensi, and Legionella feelei have been reported from Ontario (16)(17)(18)(19)(20)(21); L pneumophila serogroup 1 from Manitoba (22); and Legionella maccachernii from Saskatchewan (23). Nicolle et al (24) reported nine patients with community-acquired Legionellosis who were hospitalized at the Health Sciences Centre in Winnipeg between 1986 and 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Aspiration of water containing Legionella has also been suggested to be a common transmission route (102), although the frequency with which this occurs is unclear. Reports have suggested that immunocompromised patients in health care settings may be at risk from contaminated respiratory equipment (103)(104)(105)(106)(107)(108); in these specific instances, the use of sterile potable water may be advised (109)(110)(111).…”
Section: Epidemiology and Diseasementioning
confidence: 99%
“…However, one study of pneumonia patients admitted to 3 acute care hospitals in Pittsburgh 6 found that 6% of patients admitted from nursing homes had Legionella infection and 6% had C pneumoniae infection. There are reports of endemic 41 and epidemic 42 Legionella infection occurring in long-term care facilities. Outbreaks of C pneumoniae infection have also been reported.…”
Section: E T I O L O G Ymentioning
confidence: 96%